Newspaper preservation and access - Gibb, Ian P.; International Federation of Library Associations and Institutions (München : New York : K.G. Saur, 1988)
Discusses issues relating to history and use of the press, and preservation and access to newspapers.
Volume I.
Edited for the Section on Serial Publications and the Working Group on Newspapers.
Proceedings of the symposium held in London, August 12-15, 1987.
Includes bibliographical references.
kjo 16/01/2019
Loans
Keywords: Presevation; Libraries; Newspapers; Newspaper and periodical libraries; Serials control systems; Newspapers in microform